2004
DOI: 10.1021/bi0490439
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of a Flavin-Dependent Thymidylate Synthase

Abstract: The ThyA gene that encodes for thymidylate synthase (TS) is absent in the genomes of a large number of bacteria, including several human pathogens. Many of these bacteria also lack the genes for dihydrofolate reductase (DHFR) and thymidine kinase and are totally dependent on an alternative enzyme for thymidylate synthesis. Thy1 encodes flavin-dependent TS (FDTS, previously denoted as TSCP) and shares no sequence homology with classical TS genes. Mechanistic studies of a FDTS from Thermotoga maritima (TM0449) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
114
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(136 citation statements)
references
References 17 publications
14
114
8
Order By: Relevance
“…In the alternative pathway, ThyX performs the transfer without oxidation of tetrahydrofolate, utilizing both dUMP and methylenetetrahydrofolate as reactants and FAD and NADPH in the redox phase of the reaction (1,10,17,22,23). Whereas ThyA requires a companion enzyme, dihydrofolate reductase, to regenerate tetrahydrofolate that has been oxidized in the transfer reaction, ThyX requires dUMP, NADPH, FAD, and methylenetetrahydrofolate (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the alternative pathway, ThyX performs the transfer without oxidation of tetrahydrofolate, utilizing both dUMP and methylenetetrahydrofolate as reactants and FAD and NADPH in the redox phase of the reaction (1,10,17,22,23). Whereas ThyA requires a companion enzyme, dihydrofolate reductase, to regenerate tetrahydrofolate that has been oxidized in the transfer reaction, ThyX requires dUMP, NADPH, FAD, and methylenetetrahydrofolate (3).…”
Section: Discussionmentioning
confidence: 99%
“…In ThyX enzymes, the conversion of dUMP to dTMP involves two half reactions, oxidation and transfer of the methylene group from dUMP to form the dTMP final product (1). To test the ability of the ThyX mutants to execute these essential half reactions, two biochemical assays were performed.…”
Section: Formation Of Higher-order Complexesmentioning
confidence: 99%
“…This observation led to the identification of alternative flavin-dependent thymidylate synthases (FDTSs), which are encoded by the thyX gene and have no sequence or structure homology to classic TSase enzymes (2,6,7). Furthermore, multiple studies have identified key differences in the molecular mechanism of catalysis between FDTSs and classic TSases (2,4,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These differences, along with the fact that the thyX gene is present in many human pathogens (e.g., bacteria causing Anthrax, Tuberculosis, Typhus, and other diseases), renders these flavo-enzymes as potential targets for rational inhibitor design, possibly affording compounds that might be effective antimicrobial drugs (11,(22)(23)(24).…”
mentioning
confidence: 99%
“…Although the reductive halfreaction is activated by dUMP the conversion of dUMP to dTMP occurs during the oxidative half-reaction (FADH 2 →FAD) (8,10,14,18,27). In contrast to classic TSase, where the cofactor CH 2 H 4 folate provides both the H − and methylene, in the FDTS reaction the H − is provided by the FADH 2 and CH 2 H 4 folate is used only as a source for the methylene moiety (18,20,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation